The American Vietnam war veterans’ reactions to the Vietnam war 50th anniversary commemoration = Phản ứng của cựu chiến binh mỹ trong chiến tranh Việt Nam tới sự kiện kỉ niệm 50 năm ngày chiến tranh Việt Nam - Triệu, Thị Vân Trang (2021)
The issue of the American public opinion towards the Vietnam War, one of the most controversial and unpopular conflicts in the U.S. history, has been approached by scholars and historians. Throughout the years, it is proved that the American remained deeply divided over the nature and reality of the war, as well as its impacts on the nation’s foreign policies. As the 21st century progresses, nearly half a century since the ground battle in Vietnam started, the U.S. Department of Defense officially launched the Vietnam War 50th Anniversary Commemoration, once again dismaying their citizens including thousands of veterans of the war. This thesis aims at addressing a particular side of this issue: the American Vietnam War veterans’ reactions to the war 50th Anniversary together with the explanation of the reasons underlying their responses. The results of this research may act as a good reference for teachers and students majoring in American Studies, or ones interested in this specific field. As for methods of elaboration, the researcher collected data by gathering veterans’ thoughts and opinions released in various online newspapers and print ones. Then, different waves of response towards the event were figured out together with the justification of latent causes underlying them. The findings show that on the whole the disapproval sentiment among Vietnam veterans towards this postwar event outweighed that of approval. Inaccurate historical facts about the war, unattainable objectives of the commemoration, and negative educational impact on the American youth were the primary causes of opposition to the event. Still, a minority of Americans reacted positively to the project for the explanation that the commemoration may be a good chance for the country to honor and thank veterans of the Vietnam War.